2007
DOI: 10.1038/sj.embor.7400893
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sec24 isoforms in selective export of membrane proteins from the endoplasmic reticulum

Abstract: Sec24 of the COPII (coat protein complex II) vesicle coat mediates the selective export of membrane proteins from the endoplasmic reticulum (ER) in yeast. Human cells express four Sec24 isoforms, but their role is unknown. Here, we report the differential effects of Sec24 isoform‐specific silencing on the transport of the membrane reporter protein ERGIC‐53 (ER–Golgi intermediate compartment‐53) carrying the cytosolic ER export signals di‐phenylalanine, di‐tyrosine, di‐leucine, di‐isoleucine, di‐valine or termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
169
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(175 citation statements)
references
References 19 publications
(23 reference statements)
5
169
0
Order By: Relevance
“…Four Sec24 isoforms, designated Sec24A-D, are expressed in mammalian systems (54) and proteins with close sequence matches to all four human Sec24 proteins are present in the chicken database. Human Sec24 isoforms show different but overlapping cargo binding preferences, and Sec24A is most important for ER export (55). It is possible that a functional difference between Sec24 proteins exists in DT40, and Sec23 is more greatly associated with another isoform rather than the Sec24C homolog we identified.…”
Section: Resultsmentioning
confidence: 83%
“…Four Sec24 isoforms, designated Sec24A-D, are expressed in mammalian systems (54) and proteins with close sequence matches to all four human Sec24 proteins are present in the chicken database. Human Sec24 isoforms show different but overlapping cargo binding preferences, and Sec24A is most important for ER export (55). It is possible that a functional difference between Sec24 proteins exists in DT40, and Sec23 is more greatly associated with another isoform rather than the Sec24C homolog we identified.…”
Section: Resultsmentioning
confidence: 83%
“…In yeast cells, the deletion of LST1, encoding an isoform of Sec24, inhibits the trafficking of Pma1p from the ER but does not affect the trafficking of other proteins (Roberg et al, 1999). In animal cells, Wendeler et al (2007) reported the differential effects of Sec24 isoform-specific silencing on the transport of membrane proteins. Similarly, in Arabidopsis, multiple isoforms of Sec24 exist, supporting the possibility that multiple types of COPII vesicles also exist in plant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one possible explanation for the differential inhibition is that plant cells may contain multiple types of COPII vesicles that are differentially used depending on the cargo proteins. Indeed, in animal cells and yeast cells, multiple types of COPII vesicles exist (Tang et al, 1999;Wendeler et al, 2007). Among COPII vesicle components, Sec24 plays a critical role in selecting cargo proteins for the COPII vesicle (Miller et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that protein export from the endoplasmic reticulum (ER) 2 is a selective process that is mediated through COPII-coated transport vesicles and dictated by short, linear sequences called ER export motifs (1)(2)(3)(4)(5)(6)(7)(8). COPII vesicles contain a small GTPase Sar1 and the heterodimeric Sec23/24 and Sec13/31 complexes.…”
mentioning
confidence: 99%